Advances in Steel and Steel–Concrete Composite Structures : Bridging Science and Industry - Wojciech Lorenc; Dariusz Czepiżak; Piotr Kozioł; Marian A. Giżejowski; Jakub Marcinowski; Eugeniusz Hotała (Routledge, 2025)
Advances in Steel and Steel–Concrete Composite Structures: Bridging Science and Industry presents the proceedings of the 15th International Conference on Metal Structures (ICMS 2025), held on May 28–30, 2025 in Wrocław, Poland. The volume reflects the conference theme “Science for Industry” and brings together contributions from leading researchers and practitioners in structural engineering.This book gathers peer-reviewed papers covering the most recent advances in steel and steel–concrete composite structures, emphasizing the interplay between fundamental research and industrial applications. Contributions are organized into thematic sections that reflect the breadth of current developments in the field: from material properties to complex structural systems; stability and buckling of steel members; innovations in composite steel–concrete solutions; conservation and adaptation of heritage structures; structural health monitoring and digital innovation; advanced design of connections; steel and composite bridges; and thin-walled and lightweight structural systems. The volume highlights experimental investigations, analytical approaches, case studies, and applications of new standards and codes, especially in the European context. Together, these proceedings document the state of the art, illustrate best practices, and point to future directions in sustainable, safe, and efficient structural engineering.The book is intended for academics, researchers, and graduate students working in structural and civil engineering, as well as for practicing engineers and designers engaged in steel and composite construction. It also provides valuable insights for industry professionals seeking to integrate innovative research findings into engineering practice.